THE RESEARCH OF ELASTICITY AND STRENGTH OF SEEDS (Conferencea, 2023)
This article puts forward the idea of isolating seeds with residual fiber from the composition of ginned seeds using a special technology. In the course of the study, the properties of seeds were studied and rational solutions for seed treatment using this technology were found.